2011
DOI: 10.1016/j.aller.2010.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Safety of specific immunotherapy using a depigmented and polymerised extract of Dermatophagoides pteronyssinus in children under five years of age

Abstract: Specific immunotherapy in children under five years of age with the extract used is safe. We consider that further studies are needed, involving other types of extracts, to allow reconsideration of the relative contraindication of patient age for the administration of immunotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
1
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 13 publications
0
6
1
1
Order By: Relevance
“…Finally, it is difficult to exactly define the allergen concentration of an extract, and it can significantly vary between different manufacturers or even between different batches from the same manufacturer (personal communication with Stallergenes). These factors may contribute to the lower rate of AEs reported by Hernandez et al [13] than in our study. It therefore appears difficult to compare the rate of AEs between studies using different cluster regimens with different allergen extracts.…”
Section: Adverse Events During Cluster Regimencontrasting
confidence: 45%
See 1 more Smart Citation
“…Finally, it is difficult to exactly define the allergen concentration of an extract, and it can significantly vary between different manufacturers or even between different batches from the same manufacturer (personal communication with Stallergenes). These factors may contribute to the lower rate of AEs reported by Hernandez et al [13] than in our study. It therefore appears difficult to compare the rate of AEs between studies using different cluster regimens with different allergen extracts.…”
Section: Adverse Events During Cluster Regimencontrasting
confidence: 45%
“…Cluster and even rush regimens have been introduced into clinical routine for hymenoptera venom SCIT [6], but are less commonly used for aeroallergens such as house dust mites (HDM) [2] despite a safety profile comparable to conventional SCIT [3,7,8]. Cluster regimens for HDM SCIT have mainly been investigated in adult or mixed adult and pediatric study populations [3,[8][9][10][11][12], while data on pediatric populations are rarer [7,13,14]. We therefore carried out this study to assess the safety and tolerability of a cluster regimen for HDM SCIT in a pediatric population, to assess its applicability in the clinical routine of a pediatric hospital, and to identify risk factors for the development of AEs during the cluster regimen.…”
mentioning
confidence: 99%
“…The glutaraldehyde-polymerized depigmented allergen extracts show a significant decrease in specific IgE binding capacity, being more immunogenic and less allergenic, thus allowing the treatment to be initiated with higher doses, compared to the unmodified extracts, and a maintenance dose to be reached in a short period of time, potentiating the earlier onset of efficacy [ 16 ]. Several studies have shown the safety and early clinical efficacy of SCIT, using vaccines containing modified allergen extracts (depigmented and polymerized) in children and adults with allergic rhinoconjunctivitis and/or asthma with mite- and/or pollen-sensitization, most of them using conventional or cluster schedules [ 9 17 18 19 20 21 22 23 24 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…The remaining 24 full-text articles were reviewed for more detailed evaluation; 15 of them were also excluded. Of them, 4 studies were not real randomized/controlled studies [13][16], 10 studies in which some patients included were asthmatics alone without AR [17][26], and 1 study did not perform a real cluster protocol [27]. Additional, a RCT was excluded due to repeated data [28].…”
Section: Resultsmentioning
confidence: 99%